POTENSIAL MESENCHYMAL STEM CELL-DERIVED EXTRACELLULAR VESICLES (MSC-EVS) SEBAGAI TERAPI TERBARU DALAM OBAT ISKEMIK RETINAL - Sisca Sisca; Nurul Azizah; M.Salas Al Aldi (Journal Medical Universitas muhammadiyah Makassar, 2018)
Retinal ischemia (IR) is still the biggest cause of blindness in the world. Several factors contribute to the pathogenesis of Retinal Ischemia. However, oxidative stress and inflammatory processes are the main factors. Various forms of therapy have been applied in clinical care of Retinal ischemia, but none have been optimal for repairing the cells damage and able to avoid immunological and oncogenic reactions. MSC-EVs have opened a new perspective for the treatment of Retinal Ischemia. MSC is a multipotent cell with paracrine characteristic and mediated by extracellular vesicles (EVs) which is derivative of MSC that can be used as a biomimetic agent to help nerve protection and tissue regeneration. In addition, MSC-EVs have a lower tendency to trigger immune responses and the inability to directly form tumors. Therefore, MSC EVs can prove to be an ideal source for the latest therapies in dealing with the problem of retinal ischemia. This Literature Riview is compiled by using a literature study with collecting valid journals, particular inclusion and exclusion criteria. On testing its effectiveness, three indicators were used, that is the protective effect of MSC-EVs on retinal cells, the effects of post-ischemic in vivo administration of MSC-EVs, and the distribution of MSC-EVs in humour vitreous and long-term protective effects estimates. Significantly shows a protective effect, decreases inflammatory factors and apoptosis of retinal cells. Based on the results of testing in vitro and in vivo MSC-EVs are endocytosis by retinal cells that provide neuroprotective effects before and after treatment, and this effect can be developed into long-term therapy. Therefore, using MSC-EVs can be a promising therapy in the treatment of retinal ischemia.